Arabic Language Learning With Blended learning Model In Arabic Language Education Study Program - Arifudin, (Perspektif Pendidikan dan Keguruan, 2022)
The purpose of this study was to describe the implementation of learning Arabic using a blended learning model and to reveal the obstacles faced by students. This research is a field research with a qualitative descriptive method. The data collection method uses observation and interview techniques. The place of research is at the Arabic Language Education Study Program, IAIN Pontianak. The results of this study are the implementation of Arabic language learning with the Blended learning model carried out in two systems, namely the face-to-face system and the online system. Face-to-face learning is done virtually using the Google Meet application. While online learning is done using e-learning applications and You Tube. The obstacle faced by students when participating in learning is the difficulty in understanding the material, especially when learning is done online. Besides that, the limited internet network also makes students unable to take part in learning well. Learning Arabic with a blended learning model should adapt to the need for communication and interaction between educators and students in the learning process. Learning skills that are expressive should be done with a face-to-face system. Meanwhile, receptive skill learning can be done online.